Comparing real-world evidence among patients with metastatic pancreatic ductal adenocarcinoma treated with liposomal irinotecan. (August 2020) - Koeller, Jim; Surinach, Andy; Arikian, Steven R.; Zivkovic, Marko; Janeczko, Patrick; Cockrum, Paul; Kim, George
There are questions surrounding the real-world effectiveness of chemotherapeutic treatments for pancreatic ductal adenocarcinoma. This literature review compared the clinical characteristics and outcomes of available real-world evidence (RWE) for liposomal irinotecan in combination with 5-fluorouracil (5-FU) and leucovorin (LV), a treatment regimen indicated for patients with metastatic pancreatic ductal adenocarcinoma (mPDAC) who previously progressed on gemcitabine-based therapy. A targeted literature search was conducted in the PubMed Central® and Embase® databases to identify available RWE regarding patients with mPDAC receiving liposomal irinotecan published within the last 5 years (January 2014–September 2019). Data were extracted for prior lines of therapy, performance status, overall survival (OS), progression-free survival (PFS), duration of exposure, and adverse events. Six studies met inclusion criteria. A comparison of baseline patient characteristics and results with the included evidence reveals a clinically fragile, real-world patient population in terms of age (range: 61–68), prior lines of therapy with 34–61% of patients receiving ⩾2 lines of lines of prior therapy and performance status [49.8–100% of patients with Eastern Cooperative Oncology Group (ECOG) 0–1]. Studies observed wide OS (range: 5.3–9.4 months) and similar PFS (range: 2.3–4.1 months), with two studies measuring duration of exposure (7.3 weeks, 3.1 months). Patients analyzed by RWE studies tended to be older with significant disease progression, poor performance status, and more heavily pretreated compared with the phase III registrational trial (NAPOLI-1). Despite this, patients treated with liposomal irinotecan + 5-FU/LV therapy had similar outcomes as those in NAPOLI-1.